Analyzing The Ecotourism Impact Of The Mangrove Forest On The Welfare Of Kampung Nelayan In Langsa City - Fauzan, Muhammad; Sabrina, T.; Lubis, Satia Negara (CV. ARGA FARMA, 2024)
This study investigates the impact of mangrove forest ecotourism on the well-being of the fishing community in Kampung Nelayan, Langsa City, Indonesia. Mangrove forests offer both ecological and economic advantages, making their preservation vital. Ecotourism is presented as an alternative means to utilize these ecosystems, particularly in Kuala Langsa Village. Using qualitative research and IPA analysis, the study explores the factors that both support and hinder ecotourism development in this area. The strengths identified include sustainable conservation efforts and the backing of local government and agencies. However, weaknesses such as limited tourist facilities and oversight slow progress. Opportunities arise from new tourist destinations, though challenges such as inadequate infrastructure and competition within the tourism sector persist. The research underscores the importance of conserving mangrove ecosystems, advocating for sustainable practices and increased local authority support. Overcoming infrastructure hurdles is critical to enhancing mangrove ecotourism’s success in Langsa City.